Immunotherapy - Myths, Reality, Ideas, Future 2017
DOI: 10.5772/66496
|View full text |Cite
|
Sign up to set email alerts
|

CARs on the Highway: Chimeric Antigen Receptor Modified T Cells for the Adoptive Cell Therapy of Malignant Diseases

Abstract: Adoptive therapy of malignant diseases by chimeric antigen receptor (CAR) redirected T cells takes advantage of the patient's own immune system to recognize and destroy cancer cells. This is impressively demonstrated by the induction of complete and lasting remissions of leukemia with CAR-engineered T cells in early phase trials. Recent developments in optimizing the CAR design, in the recognition of target cells and the production of modified cells for clinical use, have paved the path for a broader applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 127 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…A high tumor burden often indicates a poor prognosis and significant adverse reactions after CAR-T therapy (31). It is suggested that a high tumor burden might affect the efficacy of CAR-T cell therapy (32,33). It was thus hypothesized that CAR T cells behave differently in mouse models with different tumor burdens.…”
Section: Nd-gg Car-t Cells Significantly Improved Antitumor Activity In Mouse Model With High Tumor Burdenmentioning
confidence: 99%
“…A high tumor burden often indicates a poor prognosis and significant adverse reactions after CAR-T therapy (31). It is suggested that a high tumor burden might affect the efficacy of CAR-T cell therapy (32,33). It was thus hypothesized that CAR T cells behave differently in mouse models with different tumor burdens.…”
Section: Nd-gg Car-t Cells Significantly Improved Antitumor Activity In Mouse Model With High Tumor Burdenmentioning
confidence: 99%